Determinants of Factors That Influence Income Smoothing - Novius, Andri (InJEBA : International Journal of Economics, Business and Accounting, 2023)
The aim of this research is to find out the partial and simultaneous influence of firm size, leverage, cash holding, winner/loser and profitability on smoothing in technology sector companies listed on the Indonesia Stock Exchange in 2019-2021. The method in this research uses quantitative methods. The hypothesis in this research was tested using logistic regression analysis using EViews 12 software. The sampling technique used in this research was the Purposive Sampling Technique which produced 11 samples of selected companies over a period of 3 years so that 33 sample units of companies in the technology sector were listed. on the Indonesian Stock Exchange. The results of this research show that the variables firm size, leverage and profitability have a significant effect on income smoothing. Meanwhile, cash holding and winner/loser stock do not have a significant effect on income smoothing. For the results of simultaneous hypothesis testing, firm size, leverage, cash holding, winner/loser stock and profitability have a significant effect on income smoothing. The implication of this research is that companies can first consider the impact before carrying out income smoothing.